Studi Komparasi Bahan Barium Ferrite Magnet Dan Pani/Fe₃O₄, Sebagai Radar Absorbing Material (RAM) - Elza Ully Tiara Tampubolon; Bagus Kusuma; Sovian Aritonang (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
This research examines the effectiveness of Barium Ferrite and PANI/Fe₃O₄ composite as Radar Absorbing Material (RAM) to reduce radar detection. Barium Ferrite has high absorption at high frequencies as well as good thermal stability, making it suitable for applications under extreme and long-term conditions. In contrast, PANI/Fe₃O₄ composites exhibit high flexibility, the ability to absorb waves over a wider frequency range, as well as light weight, ideal for requirements with lightweight materials, such as aircraft. The analysis shows that the selection of RAM depends on the application requirements regarding frequency range and thermal stability. This study recommends the development of composite materials that combine the advantages of both materials as well as field tests to ensure optimal performance in stealth applications.